STRATEGI PENINGKATAN JUMLAH PENDAFTAR UNTUK MENINGKATKAN PROFITABILITAS (STUDI KASUS PADA BISNIS SD BAITURRAHMAN) - Salsabila Tarisha Putri; Cecep Safa'atul Barkah (Jurnal Administrasi Bisnis Fisipol Unmul, 2021)
The marketing strategy carried out by the company has an impact called marketing performance. and evaluation of benchmarks is something that is very much needed. To get an evaluation as well as a benchmark, a marketing performance measurement is needed. One of the tools to measure marketing performance is marketing materials where in this measurement there is a calculation of financial metrics. Measurement with financial metrics is usually oriented to measuring profitability with financial ratios of profit on sales from the business carried out by SD Baiturrahman. The method used in this research is descriptive analysis research with a quantitative approach. Where this research will explore the company's performance which is calculated through the marketing metric of profit on sales. Based on this research, the marketing strategy process carried out by Baiturrahman Elementary School to increase the interest of parents to send their children to school is by conducting strategic analysis and internal and external analysis of the company, conducting strategic planning, and developing marketing programs.